Legal Analysis Of Testament Wajibah For Interfaith Heirs (Case Study: Religious Court Decision No.0554/PDT.P/2023/PA.Sby) - Pitaloka, Diva; Jumadi, Joko; Putra, Muhd. Hamka Maha; Ridwan, Ridwan; Putri, Ria Wierma (Journal of Law and Policy Transformation, 2023)
There are 3 (three) conditions that must be met in order to become an heir as regulated in Article 171 letter c of the Compilation of Islamic Law (KHI) namely that an heir is a person who at the time of death, he was related by blood or marriage to the testator, was a Muslim and was not prevented by law from becoming an heir. As in case number 0554/Pdt.P/2023/Pa .Sby. In this decision the Panel of Judges granted the applicant's request and determined the applicant to be a mandatory testator. This research method is  normative legal research, conceptual approach and case approach. The result states that the judge granted the Petitioner to be the Legal Heir as a Testament Wajibah even though he had a different religion from the Muslim heir due to consideration of justice. Judges are not mouthpieces of the law, so for the sake of 'justice' judges carry out legal inroads (contra legem) into the provisions contained in the Compilation of Islam.